Influence of liquid properties on plain-jet airblast atomization - Lorenzetto, G. E. (Cranfield University, 1976)
This thesis reports the results of a detailed programme of research on airblast atomization carried out using a specially designed plain-jet atomizer in which the fuel is injected into a high velocity airstream in the form of a discrete jet. Because recent studies on airblast atomization have been mainly confined to sheet and then subjected on both sides to the atomizing action of high velocity air, information was needed to carry out a comparison between^the two mechanisms of atomization. It was in order to obtain such information that the present investigation was undertaken and the study essentially resolved into a detailed experimental exploration of the spray characteristics of 1plain-j et1 airblast atomizers. Specially prepared liquids were employed to distinguish between the separate effects on S.M.D. (Sauter Mean Diameter of spray) of viscosity, surface tension and density. The liquids employed represented a range of values of viscosity from 1 .0 to 76 x 10 Kg/ms,/while surface tension and density were varied -3 3 between 26 and 73 x 10 N/m and 794 and 218oKg/m respectively. Atomizing air velocities covered the range of practical interest to the designers of continuous combustion systems and varied between 70 and 180 m/s. The effect of scale on S.M.D. was studied using several different fuel injectors varying in orifice diameter between 0.39 and 1.58 mm. A detailed description of the light-scattering technique for drop size measurement is included...